Identifying strategies to manage boreal forests: simulating moose and timber management scenarios at a landscape scale in the face of changing environmental conditions - Nathan R. De Jager; Wiebke Neumann; Miguel M. Girona; Joakim Hjältén; Anouschka R. Hof (European Journal of Forest Research, 2025)
There are ongoing debates among different stakeholders about which forest and ungulate management strategies will sustain high levels of timber and animal harvest and maintain important ecosystem functions under climate change. Ungulate-forest interactions are complex, including periods where forest regeneration is sensitive to browsing pressure, making it difficult to predict the consequences of a given strategy over time. To aid decision-making, we simulated the impacts of moose browsing on forest succession under 18 different combinations of moose ( Alces alces ) harvest rate levels and forest management scenarios in a boreal forest landscape in southern Sweden given projected changes in forest growth due to climate change. We found that the current management practices are important for sustaining a moose-forest system. Increasing moose harvest rates led to slightly smaller moose populations, larger estimates of landscape carrying capacity, and less biomass removal of Scots pine ( Pinus sylvestris ), a commercially valuable species. However, minor changes in the moose harvest were hardly affecting timber production. Increasing the timber harvest rotation time led to the highest estimates of Scots pine biomass, while thinning younger cohorts lead to the highest estimates of Norway spruce ( Picea abies ) biomass. These changes came without much effect to moose population dynamics. However, the increased broadleaf production scenario had a very large positive effect on total aboveground live biomass of deciduous species and on landscape carrying capacity and moose density. This scenario subsequently resulted in the greatest estimates of biomass removal of Scots pine, highlighting the tradeoffs associated with increased moose production.